Revitalizing a lost space Laguna de Bay waterfront development - Paredes, Peter Dominique R.; Tomeldan, Michael (Quezon City College of Architecture, University of the Philippines Diliman, 2014)
City centers are rapidly evolving and developing. However, there are some vast areas in city centers that are underutilized and in state of blight which are commonly found in the waterfronts. These are called lost spaces. These value of spaces are underutilized and causes spatial discontinuity between the body of water and other downtown districts. However, these space offer a tremendous opportunity to be a maximized and be utilized by the community through revitalization.
This thesis seeks to provide a waterfront design that is socially-acceptable and fits the identified lost space in Binangonan, Rizal, a coastal town along Laguna de Bay. This study finds out that an in-fill district whose components are based on local realities that are anchored to the site really fits the lost space. The identified components are facilities geared to boost local tourism industry, facilities for cultural, social identity and community learning and water industry support facility.
Altogether, the infill waterfront development serves as a district that supplements the needs of the community and all in all boosts the macro-economic activity and sustainability of the downtown.
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Waterfront development -- Binangonan (Rizal) .; Waterfront -- Design